The Romance of Boys Bathing in Toronto’s Don River, 1890–1930 - Barbour, Dale (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2018)
This article uses a study of Toronto in the late nineteenth and early twentieth centuries to upend assumptions about class, the urban environment, and the presentation of the naked body. Rather than attempting to drive bathers out of urban space, the city’s middle class viewed the bathing boy through the lens of anti-modernism and turned them into pre-industrial folk figures. Puncturing the nostalgic gloss of the swimming hole allows us to see the city with new eyes. We can avoid declensionist narratives that imagined Toronto’s Don River as too polluted or too industrial for recreational use. When we follow the bathers we find that the marginal, semi-industrialized river provided an ideal recreational space that cloaked and contained the undressed male body. This project relies on newspaper accounts of drownings and rescues, municipal records, regional histories, and visual culture to recreate the social environment of early twentieth-century bathing spaces.